If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 1) = -2(x + -4) + x Reorder the terms: 7(1 + x) = -2(x + -4) + x (1 * 7 + x * 7) = -2(x + -4) + x (7 + 7x) = -2(x + -4) + x Reorder the terms: 7 + 7x = -2(-4 + x) + x 7 + 7x = (-4 * -2 + x * -2) + x 7 + 7x = (8 + -2x) + x Combine like terms: -2x + x = -1x 7 + 7x = 8 + -1x Solving 7 + 7x = 8 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + 7x + x = 8 + -1x + x Combine like terms: 7x + x = 8x 7 + 8x = 8 + -1x + x Combine like terms: -1x + x = 0 7 + 8x = 8 + 0 7 + 8x = 8 Add '-7' to each side of the equation. 7 + -7 + 8x = 8 + -7 Combine like terms: 7 + -7 = 0 0 + 8x = 8 + -7 8x = 8 + -7 Combine like terms: 8 + -7 = 1 8x = 1 Divide each side by '8'. x = 0.125 Simplifying x = 0.125
| 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 | | 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 | | 28=4b-3s | | -3+5x+30=37 | | 28=4b+3s | | -8(3+r)=32 | | 3/3-4 | | -3(2h+1)=4h-3 |